Australia : Financial Sector Assessment Program-Detailed Assessment of Observance-Basel Core Principles For Effective Banking Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This Detailed Assessment of Observance report specifies Base Core Principles (BCP) for effective banking supervision in Australia. An assessment of the effectiveness of banking supervision requires a review of the legal framework, and a detailed examination of the policies and practices of the institution(s) responsible for banking regulation and supervision. In line with the BCP methodology, the assessment focused on banking supervision and regulation in Australia and did not cover the specificities of regulation and supervision of other financial institutions. The assessment has made use of five categories to determine compliance: compliant; largely compliant, materially noncompliant, noncompliant, and non-applicable. The report insists that Australian Prudential Regulation Authority (APRA) should put more focus on assessing the various components of firms' Internal Capital Adequacy Assessment Process and other firm-wide stress testing practices. A periodic more comprehensive assessment of banks' risk management and governance frameworks will further enhance APRA's supervisory approach.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet